2021
DOI: 10.1088/1758-5090/abd159
|View full text |Cite
|
Sign up to set email alerts
|

3D cell-printing of tendon-bone interface using tissue-derived extracellular matrix bioinks for chronic rotator cuff repair

Abstract: The tendon-bone interface (TBI) in rotator cuffs exhibits a structural and compositional gradient integrated through the fibrocartilaginous transition. Owing to restricted healing capacity, functional regeneration of the TBI is considered a great clinical challenge. Here, we establish a novel therapeutic platform based on 3D cell-printing and tissue-specific bioinks to achieve spatially-graded physiology for functional TBI regeneration. The 3D cell-printed TBI patch constructs are created via a spatial arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 64 publications
1
53
0
Order By: Relevance
“…Although few studies have focused on 3D bioprinting of tendon tissue, a recently published study has demonstrated the potential of the tendon dECM (TdECM) bioink (Figure 5A) [133]. A TdECM bioink formulated from decellularized porcine Achilles tendon was used to encapsulate human bone marrow-derived mesenchymal stem cells (hBMMSCs).…”
Section: Tendonmentioning
confidence: 99%
See 2 more Smart Citations
“…Although few studies have focused on 3D bioprinting of tendon tissue, a recently published study has demonstrated the potential of the tendon dECM (TdECM) bioink (Figure 5A) [133]. A TdECM bioink formulated from decellularized porcine Achilles tendon was used to encapsulate human bone marrow-derived mesenchymal stem cells (hBMMSCs).…”
Section: Tendonmentioning
confidence: 99%
“…Therefore, bonetendon interfaces with spatially organized scaffolds equipped with drugs, genes, and cells with spatial organization must be engineered [150]. Recently, based on the flexibility of the 3D bioprinting technique, a spatially graded tendon-bone interface (TBI) patch was constructed using hBMMSC-laden TdECM and bone dECM (BdECM) bioinks in subsequent experiments [133]. Such a fibrocartilaginous construct significantly accelerates and promotes TBI healing in a rat chronic tear model, which demonstrates the regenerative potential of a tissue-specific dECM bioink-based approach.…”
Section: Interfaces Of Musculoskeletal Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofabricating a full-thickness structure (>5 mm) using alginate bioinks, uniaxial gradients of both cells and materials supported heterogeneous musculoskeletal tissue differentiation within one construct [ 210 ]. Although Chae et al biofabricated a three layered tendon implant with discrete gradients using extrusion printing; after 9 weeks of implantation in rats, these implants were remodeled to constructs with smooth transitions between the bone–tendon interface [ 211 ]. By converging melt-electrowriting with the extrusion of bioinks, de Ruijter et al, were able to observe a smooth transition between three layers of different bioinks (mixing of components across zones) although it had been printed in a layer-by-layer process with 200–400 µm diameter bioink resolution ( Figure 6 C) [ 212 ].…”
Section: Designing Musculoskeletal Bioinksmentioning
confidence: 99%
“…In vivo models have been crucial in providing insight into enthesis development pathways [10,11], but a limited number of in vitro models have been developed [12][13][14]. Driven by the high occurrence of reconstruction surgeries for ligament and tendon tissues, there has been increased interest in providing bi-and tri-phasic scaffolds as alternative grafts, including differentiating mesenchymal stem cells into two lineages within the same scaffold [13,[15][16][17][18]. A 2D zonal co-culture model between bone fibroblasts and osteoblasts with an overlapping interface has been proposed [14], but it is widely accepted that 3D scaffolds provide a more physiological microenvironment for cells [19].…”
Section: Introductionmentioning
confidence: 99%